CoO-Co nanocomposite anode with enhanced electrochemical performance for lithium-ion batteries. (10th January 2017) - Qin, Youzhi; Li, Qiang; Xu, Jie; Wang, Xia; Zhao, Guoxia; Liu, Changkun; Yan, Xu; Long, Yunze; Yan, Shishen; Li, Shandong
Graphical abstract: Highlights: Bind-free CoO-Co nanocomposite anode is fabricated by pulsed laser deposition. The nanocomposite shows an excellent lithium storage performance. Nanocrystalline structure of CoO and the presence of Co nanoparticles are responsible for the improved electrochemical performance. Abstract: CoO-Co nanocomposite films were successfully deposited at room temperature by pulsed laser deposition as an anode material for lithium-ion batteries. The prepared nanocomposite exhibited enhanced performance, such as excellent cycling stability (830 mA h g −1 at a specific current of 500 mA g −1 after 200 cycles) and high rate capability (578 mA h g −1 at 10, 000 mA g −1 ). The outstanding electrochemical performance can be ascribed to the nanocrystalline structure of CoO and the presence of Co nanoparticles, which could sustain high strain, enhance reaction kinetics and improve conductivity.